2020
DOI: 10.1037/ort0000492
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in cyberbullying from the perspective of victims and perpetrators.

Abstract: Although cyberbullying has attracted a good deal of research attention in recent years, we know much less about how cyberbullying differs by race and ethnicity, and the few studies that have examined this topic have yielded conflicting findings. In the current study, 352 White and Black respondents answered questions about their victimization and perpetration experiences with both traditional bullying and cyberbullying. More than 80% of both White and Black participants indicated that they had been victims of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
2
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 41 publications
0
12
2
6
Order By: Relevance
“…Looking at cybervictimization for specific and different motives provides a more differentiated picture as to whom and why is victimized online. These results contradict many of the research results from US samples (e.g., Wang et al, 2009;Kupczynski et al, 2013;Edwards et al, 2016;Barlett and Wright, 2018;Kowalski et al, 2020), but they are in line with a number of studies from Spain (Llorent et al, 2016;Rodríguez-Hidalgo et al, 2018;Zych and Llorent, 2021) where the ethnic composition is more similar to Germany. Similar to the results of Calmaestra et al (2020) first-generation students with migration background were the ones with the highest rates of cybervictimization regarding all motives.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Looking at cybervictimization for specific and different motives provides a more differentiated picture as to whom and why is victimized online. These results contradict many of the research results from US samples (e.g., Wang et al, 2009;Kupczynski et al, 2013;Edwards et al, 2016;Barlett and Wright, 2018;Kowalski et al, 2020), but they are in line with a number of studies from Spain (Llorent et al, 2016;Rodríguez-Hidalgo et al, 2018;Zych and Llorent, 2021) where the ethnic composition is more similar to Germany. Similar to the results of Calmaestra et al (2020) first-generation students with migration background were the ones with the highest rates of cybervictimization regarding all motives.…”
Section: Discussioncontrasting
confidence: 53%
“…One way to approach the topic of ethnicity-or race-based cyberbullying is to compare prevalence rates between different ethnic groups regarding victimization in general and to draw conclusion about the victimization of specific ethnic groups. In this line, a number of studies from the US showed that White adolescents seem to be exposed to cyberbullying more often than Asian, Black or Hispanic students (e.g., Wang et al, 2009;Kupczynski et al, 2013;Barlett and Wright, 2018;Kowalski et al, 2020). More comprehensive (narrative) literature reviews show similar results (e.g., Hamm et al, 2015;Edwards et al, 2016).…”
Section: Introductionmentioning
confidence: 93%
“…Yet other studies have found no significant differences between White and African American adolescents in the prevalence of bullying victimization (Connell et al, 2015) and online bullying victimization (Kowalski et al, 2020).…”
mentioning
confidence: 79%
“…12 With respect to race and ethnicity, a prior study of White and Black respondents observed similar cyberbullying victimization and perpetration behaviors. 13 Greater screen use is also associated with more cyberbullying since cyberbullying requires access to an electronic device. 14,15 However, there is a paucity of data on contemporary cyberbullying prevalence, also considering multiple sociodemographic characteristics, in US early adolescents, when cyberbullying behaviors may begin to develop.…”
Section: Introductionmentioning
confidence: 99%